Peer Tutoring Assisted Guided Inquiry Learning Model on Students’ Knowledge Competency of Mathematics - Putu Dian Valentina Darmayanti; I Wayan Wiarta; Ida Bagus Gede Surya Abadi (Universitas Pendidikan Ganesha, 2020)
The low competency of students’ mathematics knowledge was the main problem in this present study. It was due to the lack of effective learning models and the students in the class were still receivers, it made the students became passive. This study aimed to determine the significant influence of peer tutorings assisted guided inquiry learning models on students’ knowledge competencys in mathematics learning for the fifth grade Elementary School. The type of the research was quasi-experimental with a non-equivalent control group design. The population was 329 the fifth-grade students of Elementary School, while the sample was 66 students by using cluster random sampling techniques. The data collection applied multiple-choice test instruments. The analyzed data were normalized score gain from the results of the pretest and post-test using the t polled variance test. The results of tcount = 12,298 for dk = 64 at α = 0.05 so that the obtained ttable = 1.998. Because tcount > ttable, H0 was rejected and Ha was accepted. The average score of the experimental group normalized score was 0.753 more than the average control group was 0.559. It can be concluded that there is a significant influence of peer tutorings assisted guided inquiry learning models on the mathematics competency of the fifth grade Elementary School. The results of this study can be used as reading material to explore similar research objects.